The Effect of Emergency First Aid Simulation in Implementing Log Roll on Victims with Indications of Cervical Injury to Members of the Regional Disaster Management Agency of Jember Regency - edypurwanto, edy; Susilo, Cipto; Tribagus Hidayat, Cahya (D'Nursing and Health Journal (DNHJ), 2025)
ABSTRACT Introduction: Traumatic spinal cord injury occurs due to a sudden traumatic impact on the spine which causes fracture or dislocation of the spine. Therefore, in cases of traumatic spinal cord injury, systematic management is needed in the rescue and mobilization efforts by performing log roll maneuvers. This study aims to determine the effect of simulation in emergency first aid in the skill of carrying out log rolls on victims with indications of cervical bone injuries in Regional Disaster Management Agency members in Jember Regency. Methods: This research used a one group pretest-posttest design involving 40 Regional Disaster Management Agency members in Jember Regency. Participants were selected using total sampling techniques. Data was taken using a procedural observation sheet. Data were analyzed using the paired sample t-test. Results: The results of the study showed that more than half of them had adequate skills (52.5%) before carrying out the emergency first aid simulation (52.5%) and after that they had sufficient skills (47.5%). (22.5%) and good (30%). Statistical analysis shows that the average score before is 55.5 (SD ± 10.6) and after is 67.25 (SD ± 11.32) which shows that there is a significant effect of emergency first aid simulation on the skills of carrying out log roll on victims with indications of cervical spine injury among Regional Disaster Management Agency members (p-value: 0.000). Conclusion: Improving the skills of carrying out log rolls among Regional Disaster Management Agency members in Jember Regency means that through the simulation program they provide practical and concrete examples so that they get a more real picture and are better able to visualize and ultimately are able to properly receive all the information in the skills of carrying out log rolls on victims with indications of cervical spine injuries.